True Loves, Dark Nights: Queer Performativity and Grieving Through Music in the Work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)

Rufus Wainwright - Williams, Katherine (Equinox Publishing, 2016)
Canadian-American singer-songwriter Rufus Wainwright is famous around the world for his multi-faceted musical style, shown through both his recorded output and his engaging live performances. Katherine Williams combines aspects of his life story with scholarly readings drawn from several methodologies.